2021
DOI: 10.1088/1755-1315/779/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals on physiological and histological status in liver of common carp Cyprinus carpio, reared in cages and wild in the Euphrates River, Babil / Iraq.

Abstract: The current study was conducted to examine the concentrations of some heavy metals (Fe, Zn, and Cu) in sediments, chemical and physical properties of water(Temperature, pH, Salinity, Total dissolved solid, Dissolved oxygen, Biological oxygen demand5, Alanin transporter enzyme, aspartase transporter enzyme, Alkaline phosphatase, and histological effects of the studied metal on liver of 96 cage fish and wild fish 4 fish per site Cyprinus carpio (Common carp) in the Euphrates River from October of 2018 until Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…fish have the ability to accumulate heavy metals in their tissues at higher levels than environmental concentrations due to absorption along the gill surface and the kidney, liver, and gut tract wall 49 . Heavy metal accumulation by organisms can be passive or selective, and differences in heavy metal accumulation by organisms can be due to differences in assimilation, egestion, or both 50. Many studies estimated the concentration of some heavy metals (cadmium, lead, zinc, iron, manganese, selenium and nickel) in the mussels offish species and other aquatic biota collected from Euphrates river / middle of Iraq [51][52][53][54][55] . The results of the physicochemical properties of Musayyib River branched from Euphrates river revealtemporal and spatial variations during the study period, as well as seasonal and site-specific fluctuations in heavy metal concentrations.…”
Section: Heavy Metal In Fishmentioning
confidence: 99%
“…fish have the ability to accumulate heavy metals in their tissues at higher levels than environmental concentrations due to absorption along the gill surface and the kidney, liver, and gut tract wall 49 . Heavy metal accumulation by organisms can be passive or selective, and differences in heavy metal accumulation by organisms can be due to differences in assimilation, egestion, or both 50. Many studies estimated the concentration of some heavy metals (cadmium, lead, zinc, iron, manganese, selenium and nickel) in the mussels offish species and other aquatic biota collected from Euphrates river / middle of Iraq [51][52][53][54][55] . The results of the physicochemical properties of Musayyib River branched from Euphrates river revealtemporal and spatial variations during the study period, as well as seasonal and site-specific fluctuations in heavy metal concentrations.…”
Section: Heavy Metal In Fishmentioning
confidence: 99%
“…Increase in ALT concentrations may refer to the deterioration of hepatocytes as well as muscle deformities and disorders to other tissues secreting ALT. The elevation of AST suggests stress and more demand of tissue for energy (Alshkarchy et al., 2021). Increased AST and ALT activity was observed in liver tissues of Cyprinus carpio on exposure to lead acetate (Baghshani & Shahsavani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in ALT concentrations may refer to the deterioration of hepatocytes as well as muscle deformities and disorders to other tissues secreting ALT. The elevation of AST suggests stress and more demand of tissue for energy (Alshkarchy et al, 2021).…”
Section: E X H I B I Tmentioning
confidence: 99%
“…Fatima and Usmani (2013) reported that exposure of fishes (Channa striatus and Heteropneustes fossilis) to heavy metals including Cr showed various histological alterations in liver including vacuolization and hemorrhages. Alshkarchy et al (2021) investigated the histopathological effects of Zn, Fe and Cu on the liver of the Euphrates River's C. carpio. Major histopathological changes in liver were disintegration of the hepatocytes with spaces between the cells and several areas filled with degraded cells from the visceral tissues.…”
Section: Histology Of Livermentioning
confidence: 99%